"The law is the law": The Malaysian police readiness for the implementation of restorative policing. (December 2021) - Mohammad, Taufik; Gearhart, Michael C.
Abstract: In Malaysia, restorative justice is a relatively new concept in its criminal justice system and assessing the readiness of police officers in accepting the implementation of restorative justice in the police departments (i.e., restorative policing) is crucial. In this qualitative study, 28 police officers were interviewed regarding their readiness to accept the roles to implement restorative justice through the exploration of three key themes: ownership of crime, police culture, and acceptance of new roles. Our findings indicated that their readiness on the implementation of restorative justice appeared to have patterns which are categorized into cautious, in-the-box, and balanced. The different patterns of readiness provide illumination into implementing restorative policing in Malaysia through the different types of resistance shown. The findings indicate that top-down and bottom-up implementation policies are useful as they can foster shared valued among the police within their departments and the police and the communities.